Antiproliferative activity of O4-benzo[c]phenanthridine alkaloids against HCT-116 and HL-60 tumor cells. Issue 14 (15th July 2015) - Hatae, Noriyuki; Fujita, Erina; Shigenobu, Saori; Shimoyama, Sayumi; Ishihara, Yuhsuke; Kurata, Yuhki; Choshi, Tominari; Nishiyama, Takashi; Okada, Chiaki; Hibino, Satoshi
Graphical abstract